DIAGNOSTIC ACCURACY OF TIRADS CLASSIFICATION IN DIFFERENTIATING BENIGN AND MALIGNANT THYROID NODULES KEEPING FINE NEEDLE ASPIRATION CYTOLOGY (FNAC) AS GOLD STANDARD - SAQIB , HA; SAEED , U; ZAHRA , M; NOREEN , A; FIRDOUS , A; ISLAM , ZU (Biological and Clinical Sciences Research Journal, 2024)
Thyroid nodules represent a joint clinical presentation of various benign and malignant thyroid diseases. Diagnostic ultrasound, particularly utilizing the Thyroid Imaging Reporting and Data System (TI-RADS), has emerged as a pivotal tool for stratifying the risk of malignancy in thyroid nodules and guiding decisions regarding fine-needle aspiration biopsy (FNAC). However, comprehensive validation studies are warranted to assess the diagnostic accuracy of ultrasound-based TI-RADS classification compared to FNAC as the gold standard. This cross-sectional validation study, conducted at the Department of Radiology, CPE Institute of Cardiology Multan from August 2, 2021, to February 1, 2022, enrolled 243 patients presenting with thyroid nodules, including multiple and solitary nodules. Baseline demographic variables, including age, gender, and nodule duration, were recorded for each participant. Ultrasonography was performed in all patients, and TI-RADS scores were calculated. Subsequently, fine-needle aspiration biopsies, guided by ultrasound, were obtained in the radiology department and sent to the histopathology department for confirmation of malignancy. The mean age of the cohort was 42.05 ± 12.27 years, with a mean nodule duration of 6.87 ± 3.56 months. The mean TI-RADS score was 3.46 ± 2.00. Of the participants, 176 (72.43%) were male and 67 (27.57%) were female. Malignancy was detected in 84 (34.57%) patients based on TI-RADS score, whereas FNAC confirmed malignancy in 50 (20.58%) patients. Evaluating diagnostic accuracy with FNAC as the gold standard, the TI-RADS score demonstrated a sensitivity of 84.0%, specificity of 78.2%, positive predictive value (PPV) of 50.0%, and negative predictive value (NPV) of 95.0%. Our findings indicate that the TI-RADS scoring system is reliable in predicting malignancy in patients with thyroid nodules. With a sensitivity of 84.0% and specificity of 78.2%, TI-RADS represents a valuable adjunctive tool in the diagnostic algorithm for thyroid nodules, offering considerable potential for improved clinical decision-making and patient management strategies.